Identification of a Methylation-Regulating Genes Prognostic Signature to Predict the Prognosis and Aid Immunotherapy of Clear Cell Renal Cell Carcinoma - Zhang, Li; Su, Zhixiong; Hong, Fuyuan; Wang, Lei (Frontiers in Cell and Developmental Biology, 2022)
Background and Aim: Methylation is one of the most extensive modifications of biological macromolecules, affecting cell-fate determination, development, aging and cancer. Multiple methylation modifications, including 5-methylcytosine, N6-methyladenosine, have been shown to play an essential role in many cancers. However, little is known about the relationship between methylation and prognosis of clear cell renal cell carcinoma (ccRCC). In this study, we established a methylation-regulated genes prognostic signature (MRGPS) to predict the prognosis of ccRCC patients. Materials and Methods: ccRCC samples were obtained from The Cancer Genome Atlas. methylation-regulated genes(MRGs) were downloaded from the gene set enrichment analysis website, and differentially expressed genes (DEGs) and cluster analysis were used to select candidate genes. Subsequently, MRGPS were established and validated to predict the overall survival of ccRCC patients, and this was also verified in 15 ccRCC samples from the Fujian Provincial Hospital (FPH) using quantitative real-time transcription qRT-PCR. Results: In total, 95 MRGs were identified as DEGs1 between tumor and normal tissues, and 17 MRGs were identified as DEGs2 between cluster 1 and 2. Thirteen intersection genes between DEGs1 and DEGs2 were identified as hub genes, and three genes (NOP2, NSUN6, and TET2) were identified to establish MRGPS with their coefficients, using multivariate Cox regression analysis (all P<0.05). Receiver operating characteristic curve analysis confirmed good prognostic performance of the current MRGPS. Multivariate analysis revealed that MRGPS were also an independent risk factor associated with ccRCC prognosis (P<0.05). Higher NOP2 and NSUN6 expression and lower TET2 expression were found in tumor tissues compared with normal tissues of ccRCC samples. MRGPS were also associated with tumor immune microenvironment characteristics and ICIs response, and data from “IMvigor 210” showed that patients with low MRGPS would benefit more from atelozumab (P<0.05). Conclusion: The current MRGPS comprising of NOP2, NSUN6, and TET2 could not only be used as an alternative prognostic biomarker for ccRCC patients, but also as a promising index for personalized ICI treatment for ccRCC.